Developing Public Sector Transparency Measures in Thailand. (2nd January 2023) - Tamronglak, Amporn
Abstract: As part of Thailand's ongoing administrative reform, the objective of this study is to identify appropriate transparency measures for the public sector. Constructing a conceptual framework based on David Heald's anatomy of transparency complexity and Bauhr & Grimes' study, as well as practices widely accepted around the world in countries such as the United States of America, Thailand FOIA, and transparency assessment tools in Thailand, to derive appropriate measures for assessing transparency practices in Thai public agencies with regard to the term's foundation, applicability in practice, and comprehensibility. The author provides seven primary indices for evaluating the transparency of Thai government agencies.